Effect of Gastrointestinal Surgical Manipulation on Metabolic Syndrome: A Focus on Metabolic Surgery. (22nd October 2012) - Rizzello, Mario; De Angelis, Francesco; Campanile, Fabio Cesare; Silecchia, Gianfranco
Abstract : Metabolic syndrome is strictly associated with morbid obesity and leads to an increased risk of cardiovascular diseases and related mortality. Bariatric surgery is considered an effective option for the management of these patients. We searched MEDLINE, Current Contents, and the Cochrane Library for papers published on bariatric surgery outcomes in English from 1 January 1990 to 20 July 2012. We reported the effect of gastrointestinal manipulation on metabolic syndrome after bariatric surgery. Bariatric surgery determines an important resolution rate of major obesity-related comorbidities. Roux-en-Y gastric bypass and biliopancreatic diversion appear to be more effective than adjustable gastric banding in terms of weight loss and comorbidities resolution. However, the results obtained in terms of weight loss and resolution of comorbidities after a "new bariatric procedure" (sleeve gastrectomy) encouraged and stimulated the diffusion of this operation.